My Havana : the musical city of Carlos Varela - Dubinsky, Karen; Cumaná, María Caridad, 1964-; Reloba, Xenia; Arazoza, Ana Elena (University of Toronto Press, 2014)
For more than thirty years, musician Carlos Varela has been a guide to the heart, soul, and sound of Havana. My Havana is a lyrical exploration of Varela's life and work, and of the vibrant musical, literary, and cinematic culture of his generation.